Digitization of military records in Ukraine: legal problems and ways to solve them - I. V. Panova (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to a scientific study of the practice of maintaining military records of conscripts, persons liable for military service and reservists in Ukraine and identifying the main practical problems of processing conscripts’ data in electronic form, including under martial law. The main goal of the article is to establish certain problems of maintaining the Unified State Register of conscripts, persons liable for military service and reservists and ways to solve them. The methodology of the research is based on the method of system analysis, comparative and special legal methods.